Tanjung Boleng Tourism Village Development as A Tourism Destination Based on Community Based Tourism in West Manggarai - Naingalis, Elisabeth Yolanda; Negarayana, Ida Bagus Putra; Dianasari, Dewa Ayu Made Lily (Jurnal Penelitian Pariwisata, 2022)
One of the Super Priority Tourist Destinations is Labuan Bajo which has the Tanjung Boleng Tourism Village, which currently has problems regarding community participation. CBT-based tourism development in Tanjung Boleng Tourism Village needs to be implemented to increase local community participation in tourism development. This study aims to determine the development of Tanjung Boleng Tourism Village as a Community-Based Tourism Destination. This study uses qualitative data types with data collection techniques in the form of interviews, observation, documentation, and literature study. Determination of informants in this study using purposive sampling and accidental sampling. The informants in this study were the Head of the Tanjung Boleng Tourism Village Pokdarwis, the Tanjung Boleng Tourism Village Head, representatives from the West Manggarai Tourism and Culture Office, representatives from NGOs, and the Tanjung Boleng tourism village community. The results show that the development of Tanjung Boleng Tourism Village as a tourism destination based on Community Based Tourism currently needs to be improved from the economic, political, environmental, cultural, and social components by increasing human resources and managers. Tanjung Boleng Tourism Village also needs to hold key principles and elements in developing Community-Based Tourism. Keywords: Community Based Tourism, Tourism Development, Tourism Village